2021
DOI: 10.3899/jrheum.200842
|View full text |Cite
|
Sign up to set email alerts
|

Improved Incidence of Cardiovascular Disease in Patients With Incident Rheumatoid Arthritis in the 2000s: A Population-based Cohort Study

Abstract: Objective To assess trends in incidence of cardiovascular disease (CVD) and mortality following incident CVD events in patients with rheumatoid arthritis (RA) onset in 1980- 2009 versus non-RA subjects. Methods We studied Olmsted County, Minnesota residents with incident RA (age ≥ 18 years, 1987 ACR criteria met in 1980-2009) and non-RA subjects from the same source population with similar age, sex and calendar year of index. All subjects were followed until death, migration, or 12/31/2016. Incident CVD events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Given the small total number of mortality events (83 RA, 57 non-RA), this finding could again reflect insufficient power to detect a difference. This report by Myasoedova, et al 8 adds to the growing data suggesting that CV event rates-AMIs in particular-are declining in successive incident RA cohorts, but leaves open questions about whether the gaps in CV event rates and CV mortality rates between RA and non-RA are truly declining. Other reports of CV event rates in RA vs non-RA comparators that include time periods after 2000 are scarce.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…Given the small total number of mortality events (83 RA, 57 non-RA), this finding could again reflect insufficient power to detect a difference. This report by Myasoedova, et al 8 adds to the growing data suggesting that CV event rates-AMIs in particular-are declining in successive incident RA cohorts, but leaves open questions about whether the gaps in CV event rates and CV mortality rates between RA and non-RA are truly declining. Other reports of CV event rates in RA vs non-RA comparators that include time periods after 2000 are scarce.…”
mentioning
confidence: 81%
“…What could be the explanation for the discrepancy in results between the Myasoedova study 8 showing closing of the CV gap in recent decades, compared to the Yazdani 9 and Holmqvist 7 studies, which did not? All were population-based studies with matched comparators, but the Holmqvist 7 and Yazdani 9 studies had much larger sample sizes that yielded significantly higher numbers of CV events than Myasoedova, et al 8 Thus, the lack of a statistically significant difference in CV event rates between the RA and non-RA groups in the 2000s vs the 1980s in the Myasoedova study 8 may have been due to inadequate power. A strength of the Myasoedova study was that all AMIs were adjudicated by a cardiologist, whereas the other 2 studies utilized International Classification of Diseases codes for AMI diagnosis, although the latter 2 studies reported excellent positive predictive values for this methodology.…”
mentioning
confidence: 92%
See 3 more Smart Citations